Inti Pemikiran Mitologi (Tuhan, Manusia, Alam) - Eni Misna; Amalia Majid; Faliha Aulia Siregar; Heru Syahputra (Journal on Education, 2025)
This article explores the integral relationship between God, humans, and nature from classical to modern philosophical perspectives. Using a literature analysis approach, this research describes the concept of God as Causa Prima, humans as caliphs, and nature as God's creation which is a medium of knowledge. Emphasis is placed on divine philosophy, which proves the existence of God through ontology, cosmology and teleology approaches. Humans, as two-dimensional creatures with physical and spiritual aspects, are given the mandate to protect and preserve nature. The study also covers the development of Greek to modern cosmological thought, such as the "Creatio ex Nihilo" theory which debates the origins of the universe. Through this analysis, this article emphasizes the importance of understanding the relationship between God, humans, and nature to create cosmic harmony.